Association between dietary vitamin E and osteoporosis in older adults in the United States - Zhuang, Ruoyu; Hou, Wei; Zhang, Ting; Wang, Tao (Frontiers in Endocrinology, 2024)
Background: Increased oxidative stress due to aging can lead to increased bone loss. The most abun-dant form of vitamin E, namely α-tocopherol, has high antioxidant properties and biological activity; however, its effect on osteoporosis has not been well studied in humans. We aimed to investigate the association between dietary vitamin E (α-tocopherol) and osteoporosis among older adults in the United States. Methods: This cross-sectional study analyzed data on older adults in the United States aged ≥50 years from the 2007–2010, 2013–2014 and 2017–2020 pre-pandemic cycles of the National Health and Nutrition Examination Survey. Sample-weighted multivariate regression models were used, with adjustments for relevant confounders. Results: This study comprised 5,800 individuals with available data on dietary intake and bone mineral density of hip and spine. The mean participant age was 61.4 (standard deviation, 8.7) years, and approximately 9.9% had osteoporosis. High vitamin E intake was significantly associated with a reduced risk of osteoporosis (odds ratio, 0.96, 95% confidence interval, 0.93–0.98). In addition, there was evidence of interaction between dietary vitamin E and prior fracture on preventing osteoporosis. Conclusions: Our study indicated a linear association between dietary vitamin E levels and osteoporosis in an older population in the United States. Further research is required to explore the potential effects of different forms of vitamin E on osteoporosis.